Research of the performance indicators of printing impressions on cardboard for packaging production - Havenko, Svitlana; Koniukhova, Ivanna (Eastern-European Journal of Enterprise Technologies, 2025)
In modern packaging production, a diverse range of cardboards is used. Therefore, the current problem is the choice of cardboards to ensure the functional purpose of packaging. The object of the study was printing impressions for the production of cardboard packaging. Methods for studying the operational properties of cardboards that arise during the use of packaging are proposed. Based on the conducted electron microscopic studies, the influence of the structural structure of cardboards on the mechanical and physicochemical properties of printing impressions has been confirmed. The presence of waste paper and mechanical pulp in the cardboard structure increases the water absorption rate of the printing impression. The value of the relative tensile deformation of cardboard in the transverse and longitudinal directions has been determined. It has been found that with an increase in the tensile value, the ability of packaging to compensate for mechanical loads without destruction increases. The maximum anisotropy coefficient and compression modulus of cardboard impressions have been calculated. When ensuring the safety of packaged products, problems arise related to the appearance of solvent migration from printed images on packages. Chromatographic studies have confirmed that with an increase in the number of coated layers on the surface of offset impressions, the migration of paint solvents to the contents of the packages decreases. This allows the selection of cardboard for the manufacture of packages taking into account their structural structure. The results obtained make it possible to improve the technological process of manufacturing cardboard packages, ensuring their environmental friendliness and consumer properties according to their functional purpose